G70(P) Biochemical bone profiling in children with fractures suspicious of non-accidental injury (NAI). (24th May 2017) - Lewis, LB; Alison, L; Bishop, N
Abstract : Background: The RCPCH 2013 Child protection companion state that all children under 2 years who have fractures suspicious of NAI should have bone profile, vitamin D and PTH checked. This is to look for any biochemical evidence of an underlying metabolic bone disorder. Objectives: We conducted an audit to review our compliance to these guidelines and also to look at the test results to gather data in this area. Methods: A retrospective audit was conducted. Children who had a skeletal survey for suspected NAI, between August 1 s 2013 and August the 1 s 2015 were identified using our radiology database. Our laboratory database was used to identify test results and if required, case notes were reviewed. Approval from our clinical governance department was obtained. Results: Ninety six individual cases were identified as suitable for review and 35 of these had fractures. Of these 35, 97% had bone profile, 94% had Vitamin D and 80% had PTH done. Bone profile was normal in all but two of these patients. All children without a fracture had normal bone profiles. The number of children with vitamin D levels that was less than adequate was similar in both groups. Nine children had PTH levels>50 ng/L, and 8/9 had fractures. There seemed to be no correlation between Vitamin D levels and ALP. Discussion: From an audit perspective, this shows that we are greater than 94% compliant with performing bone profile and Vitamin D. Our results suggests no difference in bone profile and Vitamin D results in those with and without fractures. However PTH was raised more in those with fractures. More research is needed to see if this is consistent and if so then raises the question of which came first, raised PTH or fracture? What is the significance of this?